India: Agriwatch - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Agriwatch provides agricultural information and analyses for farmers, traders, processors and inputs suppliers to promote the production of and trade in agricultural commodities.